The effects on critical load of metal-matrix composite plates with a hole under in-plane loadings - Okumus, F.; Turgut, A. (American Society of Mechanical Engineers (ASME), 2001)
Metal-matrix composite plates consists of several layers of unidirectionally reinforced, fibrous composite laminae which have different in-plane orientations and are bonded together in a certain stacking sequence. Thus, they provide new materials with superior properties of high strength and stiffness. This study deals with analysis of rectangular metal-matrix composite laminates with circular holes under in-plane static loadings. The first-order shear deformation theory is employed in mathematical formulation. The effects on critical load by hole size, ply lamination geometry, plate thickness ratio, loading types and material modulus ratio have been investigated. The finite element method is used for finding critical loads. Numerical solutions are given in graphical forms. Copyright © 2001 by ASME
ASME 2001 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, IDETC-CIE 2001 -- 9 September 2001 through 12 September 2001 -- Pittsburgh -- 164952
Keywords: Design; Laminated composites; Plates (structural components); Reliability analysis; Shear deformation; Stress analysis; Fibrous composites; First-order shear deformation theory; In-plane orientation; Inplane loading; Lamination geometry; Mathematical formulation; Numerical solution; Stacking sequence; Metallic matrix composites